PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) DI PEMBIBITAN UTAMA YANG DIBERI TRICHOKOMPOS DENGAN DOSIS YANG BERBEDA - Aditya, Andreas F; Ali, Muhammad; Khoiri, M. Amrul (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The aim of this research is to determine the effect of application of Trichocompost and to get the best dosage on the growth of young oil palm plants in main nursery stage. The research was conducted at the experimental unit of Agriculture Faculty, University of Riau from May to August 2014. This researchwas arranged experimentally using Completely Randomized Design(CRD), consistins of5 treatment sandeach treatment repeated 3times. The treatments are dosage of Trichocompost: without application Trichocompost (T0), application Trichocompost 25 g/polybag (T1), 50 g/polybag (T2), 75 g/polybag (T3), and 100 g/polybag (T4). Data were analyzed statistically using ANOVA and followedby DNMRT at level of 5%. Parameters measured were :the increase of plants height,  increase of leaves number, increase of hump diameter, root width ratio and plants dry weight. The research results showed that the application of Trichocompost significantly effectedon all  observed parameters, except on the increase of leaves number of young oil palm plants seeds in main nursery stage. application Trichocompost with dosage of 75-100 g/polybag is the best to improve growth of young oil palm plant in main nursery stage.   Keywords : Dosage, main nursery, oil young palm plant, Trichocompost